Analysis of the statokinetic stability of track and field athletes with mental retardation in annual sports training cycles - Krasnoperova T.V. ,; Lukmanova N.B. ,; Bystrova M.V. ,; Beleva A.N. , (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study is to assess the statokinetic stability of athletes with mental retardation in a year-long sports training cycle using stabilometry. Methods and structure of the study. 8 men with mild mental retardation aged 23.3±2.1 years (four masters of sport and four candidates for master of sport) specializing in short-distance running took part in the scientific study. The study was conducted using the ST-150 stabilometric platform with STPL software. A two-phase Romberg test was performed during four periods of the annual sports training cycle. Friedman's test and Nemenski's post-hoc analysis were used to assess the reliability of the differences between the results. Results and conclusions. In the surveyed track and field athletes with mental retardation, statokinetic stability remained at a stable and optimal level throughout the annual sports training cycle. During the competitive period, the athletes showed better coordination of the visual, proprioceptive, and vestibular analyzers, as evidenced by the lower value of the center of pressure displacement velocity. During the special preparatory and transitional periods, an increased role of vision in maintaining statokinetic stability was identified. According to the post-hoc analysis by Nemeni (p-value < 0.05, Friedman test), significant differences were found in the parameters of the sagittal axis X and the speed of movement of the center of pressure. High activity of the systems in maintaining stability in the basic stance was observed in the competitive and transition periods, as evidenced by the energy expenditure coefficient.